Effect of exercise on depression severity in older people: systematic review and meta-analysis of randomised controlled trials. - Bridle, C; Spanjers, K; Patel, S; Atherton, N; Lamb, S (2012)
BACKGROUND: The prevalence of depression in older people is high, treatment is inadequate, it creates a substantial burden and is a public health priority for which exercise has been proposed as a therapeutic strategy. AIMS: To estimate the effect of exercise on depressive symptoms among older people, and assess whether treatment effect varies depending on the depression criteria used to determine participant eligibility. METHOD: Systematic review and meta-analysis of randomised controlled trials of exercise for depression in older people. RESULTS: Nine trials met the inclusion criteria and seven were meta-analysed. Exercise was associated with significantly lower depression severity (standardised mean difference (SMD) = -0.34, 95% CI -0.52 to -0.17), irrespective of whether participant eligibility was determined by clinical diagnosis (SMD = -0.38, 95% CI -0.67 to -0.10) or symptom checklist (SMD = -0.34, 95% CI -0.62 to -0.06). Results remained significant in sensitivity analyses. CONCLUSIONS: Our findings suggest that, for older people who present with clinically meaningful symptoms of depression, prescribing structured exercise tailored to individual ability will reduce depression severity.